Assessing the expectation and perception of international students in Singaopre higher education. - Goh, May Feng. (2008)
Our project seeks to investigate the quality of university life perceived among international students. It is based on a quantitative study on the measurement of service quality in Singapore’s university education. In particular, we will be examining the level of satisfaction by international students.